2000
DOI: 10.1106/n5e7-m37y-3mar-2kfh
|View full text |Cite
|
Sign up to set email alerts
|

Impact Monitoring of Smart Composite Laminates Using Neural Network and Wavelet Analysis

Abstract: Low-velocity impact damage is a major concern in the design of structures made of advanced laminated composites, because such damage is mostly hidden inside the laminates and cannot be detected by visual inspection. It is necessary to develop the impact monitoring techniques providing on-line diagnostics of smart composite structures susceptible to impacts. In this paper, we discuss the process for impact location detection in which the generated acoustic signals are detected by PZT using the improved neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Gaul et al (2001) applied a Gauss-Newton method to non linear least square optimization to analyze "synthetic" AE signals. Conversely, an alternative approach to model-based methods for the identification of the impact location was the artificial neural network approach (Sung et al, 2000). Despite this method is suitable for complex structure, it cannot provide an optimum solution.…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%
“…Gaul et al (2001) applied a Gauss-Newton method to non linear least square optimization to analyze "synthetic" AE signals. Conversely, an alternative approach to model-based methods for the identification of the impact location was the artificial neural network approach (Sung et al, 2000). Despite this method is suitable for complex structure, it cannot provide an optimum solution.…”
Section: Introduction and Statement Of The Problemmentioning
confidence: 99%
“…ANNs are a network of mathematical operations between an input and an output that are linked together via weighted connections [23,29,37]. ANNs can create a meta-model mapping given input and output via training using a previously known input and output data set.…”
Section: Impact Localisation Methodsmentioning
confidence: 99%
“…From previous studies [11,18,23,24,25,29,32,38], it was found that ANNs are able to accurately locate the position of an impact using input in the form of impact signal features such as ToA and signal amplitude. However, the accuracy is significantly reduced when there is variation between input features from an impact at a given location that differs from the features for the said location in the original training set.…”
Section: Impact Localisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al . used the neural network algorithm to estimate impact locations on a graphite composite plate. Sekine et al .…”
Section: Introductionmentioning
confidence: 99%